2020
DOI: 10.1021/acs.organomet.0c00528
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Mediated C–C Bond Formation via Reductive Coupling with Carbon Dioxide

Abstract: Carbon dioxide functionalization is a potentially transformative method to enhance the sustainability of carbon-based commercial chemicals. The reductive functionalization of CO2 via C–C bond forming reactions is one route to deriving structurally diverse products from this renewable resource. Despite considerable advances in catalytic CO2 reduction into smaller molecular fragments, such as CO, there remains relatively few transition metal mediated processes to elaborate CO2 via reductive C–C bond functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…We decided to use the Fe 0 fragment [(depe) 2 Fe] as a metallic Lewis base because its corresponding CO 2 adduct ( 1 ) is readily accessible [17a] and exhibits a rich carbon dioxide functionalization chemistry [17b,c] . Besides, Szymczak and co‐workers used the latter to investigate the activation of dinitrogen by push‐pull interactions [18] .…”
Section: Resultsmentioning
confidence: 99%
“…We decided to use the Fe 0 fragment [(depe) 2 Fe] as a metallic Lewis base because its corresponding CO 2 adduct ( 1 ) is readily accessible [17a] and exhibits a rich carbon dioxide functionalization chemistry [17b,c] . Besides, Szymczak and co‐workers used the latter to investigate the activation of dinitrogen by push‐pull interactions [18] .…”
Section: Resultsmentioning
confidence: 99%
“…A more recently reported Fe 0 system of the type [(depe) 2 Fe] (depe=1,2‐bis(diethylphosphino)ethane) afforded oxalate in 98 % yield in the presence of 2 equiv KC 8 in THF at 45 °C (Figure 3B8) [31] . Control experiments using KC 8 only or other Fe‐based complexes resulted in lower oxalate yields, thereby demonstrating that the [(depe) 2 Fe 0 ] species plays a key role in the reductive CO 2 coupling.…”
Section: Co2 Activation For Thermoreductive Couplingmentioning
confidence: 94%
“…Multiple type 2 CO2 activation on cerium-pyrazole complex Carmona and co-workers have described the use of an iridium complex containing a pyridylidene ligand in addition to a hydrotris(pyrazolyl)borate co-ligand (Scheme 19). Exposure to CO2 led to the formation of a carbamate complex (75). In this case, the AB unit corresponds to C-N (within the pyridylidene ligand) and the nitrogen atom acts as the nucleophile where the The Mann research group reported a cyclometallated iridium(III) complex where the AB atom bridge corresponds to a hydrazino (H2N-NH2) ligand (Scheme 20).…”
Section: Scheme 17 Selected Examples Of Type 2 Activation Of Co2mentioning
confidence: 99%
“…Bernskoetter and co-workers recently reported the synthesis of Fe(0) complex 50 containing a coordinated alkene, which promoted CO 2 fixation leading to the formation of the stable ferralactone 51 (Scheme 13). 75 The authors also prepared a Fe(0) complex containing coordinated CO 2 instead of an alkene. The use of KC 8 as a reducing agent in the presence of CO 2 (1.5 atm) led to the stoichiometric formation of acrylate salts.…”
Section: Type 1 Activationmentioning
confidence: 99%
See 1 more Smart Citation